1998
DOI: 10.1111/j.1469-7793.1998.745bv.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanism for non‐genomic action of 17β‐oestradiol on kainate‐induced currents in isolated rat CA1 hippocampal neurones

Abstract: Using whole‐cell voltage‐clamp recordings of dissociated hippocampal CA1 neurones, we demonstrated that 17β‐oestradiol rapidly potentiates kainate‐induced currents when applied either to the outside or the inside of the neurone. However, when the steroid was conjugated to bovine serum albumin (E2‐BSA), application to either the extracellular plasma membrane (E2‐BSAout) or the cytosolic side of the cell (E2‐BSAin) had no observable effect on kainate‐induced currents. However, when applied stimultaneously to bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 42 publications
1
63
0
Order By: Relevance
“…1), including the modulation of intracellular calcium [44,55,122,165,175,209] and protein kinase C (PKC; [266,276]). There is also evidence that membrane effects of estrogens can activate intracellular signaling pathways involving cyclic AMP (cAMP; [103,170,254]), protein kinase A (PKA; [104,141,266]), the "mitogen activated protein kinases" (or MAP kinases; [39,122,153,205,260,269,276]), and the tyrosine kinases [39]. The activation of these intracellular signaling pathways results primarily in phosphorylations/dephosphorylations producing different kinds of physiological responses such as the decoupling of a receptor from its effector system [141,[171][172][173] or the modulation of the catalytic activity of an enzyme [191].…”
Section: Non-genomic Effects On Cell Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…1), including the modulation of intracellular calcium [44,55,122,165,175,209] and protein kinase C (PKC; [266,276]). There is also evidence that membrane effects of estrogens can activate intracellular signaling pathways involving cyclic AMP (cAMP; [103,170,254]), protein kinase A (PKA; [104,141,266]), the "mitogen activated protein kinases" (or MAP kinases; [39,122,153,205,260,269,276]), and the tyrosine kinases [39]. The activation of these intracellular signaling pathways results primarily in phosphorylations/dephosphorylations producing different kinds of physiological responses such as the decoupling of a receptor from its effector system [141,[171][172][173] or the modulation of the catalytic activity of an enzyme [191].…”
Section: Non-genomic Effects On Cell Functionmentioning
confidence: 99%
“…Estrogen modulates electrical activity of neurons within a few seconds in some experiments [165,190,277,278] but with relatively longer latencies of up to 3-5 minutes in other biological systems [103,104,137,141,202,284]. The fastest of these effects appear to be associated with the allosteric modulations of ionotropic receptors [190,277,278], but most effects on electrical activity result from a modulation of ion channel activity through G protein linkage (for review see [132,176]).…”
Section: Non-genomic Effects On Cell Functionmentioning
confidence: 99%
“…Also, E2 potentiates non-NMDA (kainate)-mediated excitation of hippocampal CA1 pyramidal neurons via activation of a cAMP/PKA pathway Moss, 1996, Gu andMoss, 1998). Based on the findings from the hippocampal slice, it was hypothesized that E2 activates a Gs-coupled receptor on the extracellular surface of hippocampal neurons, which operates in concert with an internal action of E2 on cAMP-dependent phosphorylation (Gu and Moss, 1998). Importantly, these rapid actions of E2 on kainate-induced currents in hippocampal neurons are suggesting a novel mechanism (receptor) for the rapid actions of E2 in the hippocampus (Gu et al, 1999).…”
Section: Membrane-initiated Signaling Of E2mentioning
confidence: 99%
“…In particular, estrogens have been shown to increase the density of dendritic spines on CA1 pyramidal neurons (7). In hippocampal slices, 17␤-estradiol increases electrophysiological responses elicited by activation of both ␣-amino-3-hydroxy-5-methylisoxazole propionic acid and N-methyl-Daspartate (NMDA) receptors and the magnitude of long-term potentiation (LTP) in field CA1 (8,9). At the cellular level, numerous laboratories have shown that, in addition to direct genomic effects, 17␤-estradiol activates the extracellular regulated kinase͞mitogen-activated protein (ERK͞MAP) kinase pathway (10)(11)(12), an effect associated with the neurotrophic͞ neuroprotective actions of estrogen (13,14).…”
mentioning
confidence: 99%